Níveis nutricionais de fósforo disponível em diferentes granulometrias de fosfato para codornas japonesas em postura - Pinto, Carlos Eduardo LIno (2012)
The aim of this study was to determine the levels of available phosphorus forJapanese quail (Coturnix coturnix japonica) in the laying period. 648 Japanese quails were used producing eggs for consumption, in cages like battery, with dimensions of 0.9 x 0.33 x 0.15 m, and distributed in a completely randomized design with five treatments, eight replicates and nine hens/experimental unit. Was prepared diet based on corn and soybean meal, formulated to meet nutritional recommendations, except for available phosphorus. It contained 2900 kcal/kg, 20% crude protein, 3.05% calcium, 0.10% phosphorus, 1.05% of lysine, 0.720% methionine+cystine and threonine 0.730% digestible. To this basal diet, phosphate was added with different particle sizes (fine or coarse) and limestone, replacing the inert material in order to obtain five levels of available phosphorus (0.10, 0.20, 0.30, 0.40 and 0.50%) for each particle size used. In conclusion, the recommendation phosphorus, varies depending on the granulometry of phosphate used. Thus, for finely was found at 0.44% available phosphorus, and coarse, the level of 0.385% phosphorus for quails position in the second cycle.